Whole rock and discrete pyrite geochemistry as complementary tracers of ancient ocean chemistry: An example from the Neoproterozoic Doushantuo Formation, China. (1st November 2017) - Gregory, Daniel D.; Lyons, Timothy W.; Large, Ross R.; Jiang, Ganqing; Stepanov, Aleksandr S.; Diamond, Charles W.; Figueroa, Maria C.; Olin, Paul
Abstract: The trace element content of pyrite is a recently developed proxy for metal abundance in paleo-oceans. Previous studies have shown that the results broadly match those of whole rock studies through geologic time. However, no detailed study has evaluated the more traditional proxies for ocean chemistry for comparison to pyrite trace element data from the same samples. In this study we compare pyrite trace element data from 14 samples from the Wuhe section of the Ediacaran-age Doushantuo Formation, south China, measured by laser ablation inductively coupled plasma mass spectrometry with new and existing whole rock trace element concentrations; total organic carbon; Fe mineral speciation; S isotope ratios; and pyrite textural relationships. This approach allows for comparison of data for individual trace elements within the broader environmental context defined by the other chemical parameters. The results for discrete pyrite analyses show that several chalcophile and siderophile elements (Ag, Sb, Se, Pb, Cd, Te, Bi, Mo, Ni, and Au) vary among the samples with patterns that mirror those of the independent whole rock data. A comparison with existing databases for sedimentary and hydrothermal pyrite allows us to discriminate between signatures of changing ocean conditions and those of known hydrothermal sources. In the case of the Wuhe samples, the observed patterns for trace element variation point to primary marine controls rather than higher temperature processes. Specifically, our new data are consistent with previous arguments for pulses of redox sensitive trace elements interpreted to be due to marine oxygenation against a backdrop of mostly O2 -poor conditions in the Ediacaran ocean—with important implications for the availability of bioessential elements. The agreement between the pyrite and whole rock data supports the use of trace element content of pyrite as a tracer of ocean chemistry in ways that complement existing approaches, while also opening additional windows of opportunity. For example, unlike the potential vulnerability of whole rock data to secondary alteration, the pyrite record may survive greenschist facies metamorphism. Furthermore, early-formed pyrite can be identified through textural relationships as a proxy of primary marine chemistry even in the presence of hydrothermal overprints on whole rock chemistry via secondary fluids. Finally, pyrite analyses may allow for the possibility of more quantitative interpretations of the ancient ocean once the elemental partitioning between the mineral and host fluids are better constrained. Collectively, these advances can greatly increase the number of basins that may be investigated for early ocean chemistry, especially those of Precambrian age.